NIR-triggered tea polyphenol-modified gold nanoparticles-loaded hydrogel treats periodontitis by inhibiting bacteria and inducing bone regeneration. (January 2023) - Dong, Zhiqiang; Lin, Yiyi; Xu, Shibo; Chang, Linna; Zhao, Xingjun; Mei, Xifan; Gao, Xiuqiu
Graphical abstract: Highlights: The photothermal combination strategy based on EGCG and gold nanoparticles is a new attempt at periodontal bone repair. EGCG combined with gold nanoparticles as a nanoplatform for periodontal disease bone repair and inhibition of oral bacterial infection. The obtained hydrogel nanoplatform achieved an effective sterilization rate and promoted osteogenesis by promoting angiogenesis. Abstract: Periodontitis caused by bacteria is the most common oral disease. In the face of plaque formation, traditional scaling and antibiotic treatment can lead to gum recession, drug resistance and other side effects. The nanoplatform of multifunctional complex treatment is attractive for the treatment of periodontitis. In this study, epigallocatechin gallate (EGCG) was loaded into gold nanoparticle-modified hydrogels (E-Au@H) to achieve the synergistic functions of near-infrared (NIR) photosensitization, bactericidal and periodontal tissue regeneration. E-Au@H rapidly heats up to 50.7 °C within 5 min under NIR light irradiation, exerting a good photothermal effect, while the NIR spectrum can effectively control the release of tea polyphenols, enhance the antibacterial effect, promote angiogenesis and improve bone regeneration. In vitro studies showed that NIR-irradiated composites inhibited S. aureus, E. coli and S. aureus biofilms by 94 %, 92 % and 74 %, increased alkaline phosphatase activity 5-fold after 7 days and increased extracellular matrix mineralization rate 3-fold after 21 days. The rat periodontitis model successfully demonstrated that E-Au@H with NIR light irradiation inhibited dental plaque biofilm by 87 % and promoted alveolar bone regeneration by 38 %. The experimental results suggest that this hydrogel with a NIR-sensitive composite nanoplatform offers new possibilities for the treatment of periodontal disease.